1H and 2H NMR spin–lattice relaxation probing water: PEG molecular dynamics in solution - Clop, Eduardo Matias (2012)
Nuclear magnetic resonance spin–lattice relaxation times (T1) measurements were performed in aqueous solutions of poly(ethylene glycol) (PEG) of 6000 Da molecular mass to study the dynamical relation between PEG and water molecules at different solute concentrations. 1H–T1 experiments were carried on at a low magnetic field in the time domain (20 MHz) and at a high field (400 MHz) to obtain spectral resolution. Two contributing components were identified in each proton system, PEG and water, presenting values of T1 with very different orders of magnitude. The approximate matching between the shorter 1H–T1 values associated with water and PEG has lead us to conclude that there exists a network of interactions (hydrogen bonds) between the solute and the solvent, which results in the presence of an ordered and dehydrated structure of PEG folded or self-assembled in equilibrium with a more flexible monomer structure. Dynamic light scattering results were consistent with the formation of PEG aggregates, showing a mean size between 40 and 100 nm.